Modeling object arrangement patterns and picking arranged objects. (18th August 2021) - Nagata, Kazuyuki; Nishi, Takao
ABSTRACT: This study investigates object picking focusing on object arrangement patterns. Objects stored in distribution warehouses or stores are arranged in regular patterns, and the grasping strategy for object picking is selected according to the object arrangement pattern. However, object arrangement patterns have not been modeled for object picking. In this study, we represent objects as polyhedral primitives, such as cuboids or hexagonal cylinders, and model object arrangements by considering occlusion patterns for object model surfaces and considering whether the adjacent object occluding the surface is moveable. We define grasp patterns based on combinations of the grasp surfaces and discuss the grasping strategy when the grasp surfaces are occluded by adjacent objects. We then introduce newly developed gripper for picking arranged objects. The gripper comprises a suction gripper and a two-fingered gripper. The suction gripper has a telescopic arm and a swing suction cup. The two-fingered gripper mechanism combines a Scott Russell linkage and a parallel link. This mechanism is advantageous for the gripper in reaching narrow spaces and inserting fingers between objects. We demonstrate the picking up of arranged objects using the grippers. GRAPHICAL ABSTRACT: UF0001